PATHOGENESIS OF DIABETIC POLYNEUROPATHY AND MODERN SOLUTIONS FOR CLINICAL DIAGNOSIS - Dilmurod Do‘stmamat Oʻgʻli, Nematullayev; Umid Arzikulovich, Qodirov; Sokhiba Ziyadulloyevna, Khakimova (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Diabetic polyneuropathy encompasses a spectrum of symptoms signaling damage to nerve fibers and impaired functionality, primarily driven by prolonged hyperglycemia. Methods: This condition arises due to metabolic dysfunction in the body, often linked to decompensated diabetes mellitus, leading to progressive nerve cell deterioration. Results: : Patients exhibit reduced limb sensitivity, which, in severe cases, may escalate to complete sensory loss. Novelty: The study underscores the intricate relationship between sustained hyperglycemia and the gradual degeneration of nerve cells, highlighting the critical need for targeted interventions to prevent or mitigate nerve damage in diabetic patients.